Metabolic and senescence characteristics associated with the immune microenvironment in ovarian cancer - Xiong, Jian; Fu, Yiyuan; Huang, Jiezheng; Wang, Yibin; Jin, Xiaolong; Wan, Xiaoyan; Huang, Liu; Huang, Zheng (Frontiers in Endocrinology, 2023)
Ovarian cancer is a highly malignant gynecological cancer influenced by the immune microenvironment, metabolic reprogramming, and cellular senescence.This review provides a comprehensive overview of these characteristics. Metabolic reprogramming affects immune cell function and tumor growth signals. Cellular senescence in immune and tumor cells impacts anti-tumor responses and therapy resistance. Targeting immune cell metabolism and inducing tumor cell senescence offer potential therapeutic strategies. However, challenges remain in identifying specific targets and biomarkers.Understanding the interplay of these characteristics can lead to innovative therapeutic approaches. Further research is needed to elucidate mechanisms, validate strategies, and improve patient outcomes in ovarian cancer.